Human norovirus targets enteroendocrine epithelial cells in the small intestine - Green, Kim Y.; Kaufman, Stuart S.; Nagata, Bianca M.; Chaimongkol, Natthawan; Kim, Daniel Y.; Levenson, Eric A.; Tin, Christine M.; Yardley, Allison Behrle; Johnson, Jordan A.; Barletta, Ana Beatriz F.; Khan, Khalid M.; Yazigi, Nada A.; et al. (Nature communications, 2020)
Human noroviruses are a major cause of diarrheal illness, but pathogenesis is poorly understood. Here, we investigate the cellular tropism of norovirus in specimens from four immunocompromised patients. Abundant norovirus antigen and RNA are detected throughout the small intestinal tract in jejunal and ileal tissue from one pediatric intestinal transplant recipient with severe gastroenteritis. Negative-sense viral RNA, a marker of active viral replication, is found predominantly in intestinal epithelial cells, with chromogranin A-positive enteroendocrine cells (EECs) identified as a permissive cell type in this patient. These findings are consistent with the detection of norovirus-positive EECs in the other three immunocompromised patients. Investigation of the signaling pathways induced in EECs that mediate communication between the gut and brain may clarify mechanisms of pathogenesis and lead to the development of in vitro model systems in which to evaluate norovirus vaccines and treatment. Human norovirus pathogenesis is incompletely understood due to a lack of appropriate animal disease models. Here, Green et al. show norovirus replication in chromogranin A-positive enteroendocrine cells and other epithelial cells in tissue from a pediatric intestinal transplant recipient with severe gastroenteritis.